2015
DOI: 10.1177/0020872815584426
|View full text |Cite
|
Sign up to set email alerts
|

Social issues and post-disaster recovery: A qualitative study in an Iranian context

Abstract: The physical impacts of a disaster are usually the most obvious impacts, and they are easily measured. However, there is not sufficient in-depth understanding of social issues arising after disasters. This qualitative study explored three main concepts regarding social issues after an earthquake in an Iranian context: social vulnerability, social uncertainty and confusion, and ignorance of local social capital. Negligence of social issues after disasters leads to delays in returning back to normal life. Policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
0
36
0
1
Order By: Relevance
“…Although the short-term effect of the disasters on the physical well-being of older adults has been largely studied and proven that they are more vulnerable because of decreased sensory awareness, physical impairment, chronic medical conditions, and socioeconomic limitations experienced by many of the elderly,57 conclusions about the long-term psychological effects of natural disasters on older adults have been inconclusive. Some previous studies reported that the elderly are more likely vulnerable to psychological problems 4,8,9. However, other studies found that the elderly are less vulnerable to psychological impacts of disasters compared to younger survivors 1012…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the short-term effect of the disasters on the physical well-being of older adults has been largely studied and proven that they are more vulnerable because of decreased sensory awareness, physical impairment, chronic medical conditions, and socioeconomic limitations experienced by many of the elderly,57 conclusions about the long-term psychological effects of natural disasters on older adults have been inconclusive. Some previous studies reported that the elderly are more likely vulnerable to psychological problems 4,8,9. However, other studies found that the elderly are less vulnerable to psychological impacts of disasters compared to younger survivors 1012…”
Section: Introductionmentioning
confidence: 97%
“…In this case, older adults are among the most vulnerable groups to the immediate impact of natural disasters. Several studies have found that physical well-being of older adults is more affected by natural disasters compared with their younger counterparts 24. Although the short-term effect of the disasters on the physical well-being of older adults has been largely studied and proven that they are more vulnerable because of decreased sensory awareness, physical impairment, chronic medical conditions, and socioeconomic limitations experienced by many of the elderly,57 conclusions about the long-term psychological effects of natural disasters on older adults have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The lower psychological well-being in these areas can be justified by considering the effect of earthquake on these variables, especially missing occupations and failure to achieve job opportunities available in the region after the disaster and on the right time [21]. On the whole, it seems that the mean score differences between different subscales was not enough to produce significant difference in the total score of positive mental health between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…Given the high number of deaths and injuries among the elderly, this population deserves special attention (16,17). Likewise, according to human right laws, every person has the equal rights to protection (18).…”
Section: Contextmentioning
confidence: 99%